Prevalence of hypovitaminosis D in COVID-19 patients in the intensive care unit - Mikhail V. Bychinin (Eco-vector, 2021)
Background: The prevalence of hypovitaminosis D has not been studied in the Russian Federation for the group of patients with severe and extremely severe COVID-19 in the intensive care unit (ICU). Aims: To study the prevalence of hypovitaminosis D in patients with COVID-19 treated in the ICU and to determine the relationship between the vitamin D status and disease outcome. Methods: The retrospective study included 103 adult patients with severe and extremely severe COVID-19 hospitalized in the ICU. Results: 94% patients (n = 97) showed a significant decrease in the concentration of 25 (OH) D in their blood serum 11 ng/ml [7; 15 ng/ml]. 37% (n = 38) of patients showed vitamin D deficiency, 46% (n = 47) had severe vitamin D deficiency, 12% (n = 12) had vitamin D insufficiency, 5% (n = 6) had normal vitamin D levels. In the group of patients with vitamin D levels less than 10 ng/ml, the mortality rate was significantly higher than that in the group of patients with the levels of vitamin D exceeding 10 ng/ml (66% and 42%, p = 0.018). These two groups of patients also significantly differed in their age (p = 0.018), history of diabetes mellitus (p = 0.059), white blood cell count (p = 0.045), neutrophil to lymphocyte ratio (p = 0.017), D-dimer level (p = 0.05) and troponin T level (p = 0.054). Conclusion: A high incidence of vitamin D insufficiency in patients with COVID-19 treated in the ICU has been identified. Severe vitamin D deficiency was more often found in elderly patients with diabetes mellitus, and was associated with the increased mortality. The identified relationship of the vitamin D deficiency with the neutrophilic-lymphocytic index suggests an immuno-mediated effect on the outcome of patients with COVID-19.